Violation of Women Rights from Ancient to Modern Times In India: A Historical Analysis of Women's Rights Violation in India (Journal of Advances and Scholarly Researches in Allied Education, 2014)
It is a known fact now that Women held subservientposition in ancient and medieval Indian society. In ancient and medieval India,life of women was pathetic and they had very low status in the society.  There are many evidences of suppression andill-treatment of women in Ancient Indo-Aryan society. Most of the problems likeChild Marriages, Dowry system, Bride-Burning; No rights in their paternalproperty, Mass Wife-Burning (Jauhar) and Widow-Burning (Sati) have their rootsin ancient and medieval India.